Udział kobiet z powiatu inowrocławskiego w życiu publicznym = Participation of women in public life in Inowroclaw county - Ilieva, Margarita; Tychoniec, Alicja (Journal of Education, Health and Sport, 2015)
Ilieva Margarita, Tychoniec Alicja. Udział kobiet z powiatu inowrocławskiego w życiu publicznym = Participation of women in public life in Inowroclaw county. Journal of Education, Health and Sport. 2015;5(12):165-176. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35268 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2812%29%3A165-176 http://pbn.nauka.gov.pl/works/678884 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 10.11.2015. Revised 25.11.2015. Accepted: 10.12.2015. UDZIAŁ KOBIET Z POWIATU INOWROCŁAWSKIEGO W ŻYCIU PUBLICZNYM PARTICIPATION OF WOMEN IN PUBLIC LIFE IN INOWROCLAW COUNTY Margarita Ilieva, Alicja Tychoniec IG, WKFZIT, Uniwersytet Kazimierza Wielkiego w Bydgoszczy Streszczenie Celem artykułu jest przedstawienie wyników badań dotyczących sytuacji kobiet, ze szczególnym uwzględnieniem udziału mieszkanek powiatu inowrocławskiego w sferze społecznej. W ramach opracowania zgromadzone zostały opinie kobiet o ich udziale w życiu publicznym na terenie objętym badaniem. Tezy sformułowane w niniejszej pracy skonstruowano na podstawie uzyskanych wyników badania ankietowego. Poniżej przedstawiono otrzymane rezultaty badań pogrupowane w bloki tematyczne dotyczące podjętych zagadnień. Słowa kluczowe: kobieta, powiat inowrocławski, sytuacja społeczno-zawodowa, aktywność zawodowa, status społeczny. Abstract The purpose of this article is to present the results of the research on the situation of women, with particular emphasis on the participation of women in the social sphere of county Inowrocław residents. In the framework of the study opinions of women were gathered about their participation in public life in the area under study. Theses formulated in this work were constructed on the basis of the results of the survey. The followings are obtained results of the research. Key words: the woman, county of Inowrocław, social-professional situation, professional activity, social status.